Monitoring the Biological Aspects of Banded Archer Fish (Toxotes jaculatrix Pallas, 1767) in Bilah River, Labuhanbatu Regency, Indonesia - Rahmatul Hidayah; Siti Khadijah Harahap; Risda Kesuma Lubis; Rizka Junita; Lili Nurindah Sari; Khairul Khairul (Postgraduate, University of Mataram, 2023)
Banded archer fish (Toxotes jaculatrix Pallas, 1767) is one of the leading commodities of Indonesian ornamental fish. Its production so far is still from the catch of nature. Banded archer fish based on IUCN data has been included in the red list with the Least Concern (LC) category. Currently one of its habitats is found in the Bilah River, Labuhanbatu Regency. The purpose of the study was to information the condition of biological factors related to the relationship of weight length, sex ratio and factors of banded archer fish conditions in the Bilah River. Determination of observation station points by purposive sampling method, where in this study there are 3 stations. Fish sampling in January-March 2022. Fish are caught using splint nets. The entire number of fish caught was measured using a ruler with a length of 30 cm and weight using a digital balance sheet with a precision of 0.01 g. Next the data is tabulated and analyzed using the Microsoft Excel 2013 application. The data of the results of the study is displayed based on each month of observation. The results of the analysis of banded archer fish research data for the long weight relationship from January-March 2022 are negative alometric. The sex ratio of banded archer fish in January 2022 (0.69:1), February 2022 (0.47:1), and March 2022 (0.5:1). The value of the banded archer fish condition factor in January 2022 (1.0304), February 2020 (1.0338), and March 2022 (0.0954). It was concluded that the biological aspects of banded archer fish in the Bilah River still their growth and reproductioan.